2018
DOI: 10.1136/bmjopen-2017-020909
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes among Chinese women with and without systemic lupus erythematosus: a retrospective cohort study

Abstract: ObjectiveTo completely and quantifiably determine the effect of systemic lupus erythematosus (SLE) on pregnancy outcomes in a Chinese cohort.DesignA retrospective cohort study.SettingData were collected at a tertiary medical centre located in Shanghai, China, from September 2011 to May 2017.ParticipantsWe assigned 338 pregnant women with SLE to the study cohort and 1014 randomly selected pregnant women without SLE (three for every woman with SLE) to a comparison cohort. The relevant medical records of all preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 47 publications
7
49
4
Order By: Relevance
“…The previous studies have been reported the relapse rates ranged from 13 to 68%. Generally, the frequency of outcomes evaluated in this study is within the reported range from other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 77%
“…The previous studies have been reported the relapse rates ranged from 13 to 68%. Generally, the frequency of outcomes evaluated in this study is within the reported range from other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 77%
“…FGR is also a known risk in pregnancies complicated by SLE. Recently, Chen et al found a significant increase in the risk of FGR in women with SLE (aOR 2.24, 95% CI [1.85-2.71]; Chen et al, 2020), which is consistent with prior studies (Chakravarty, Nelson, & Krishnan, 2006;Smyth et al, 2010;Wu, Ma, Bao, Di, & Zhang, 2018). Although there are numerous etiologies of FGR, including intrauterine infections, chromosomal anomalies, and multiple gestations, FGR due to placental insufficiency in women with SLE is common (Gluhovschi, Gluhovschi, Petrica, Velciov, & Gluhovschi, 2015).…”
Section: Fetal Growth Restrictionsupporting
confidence: 59%
“…in contemporary studies. [8][9][11][12]29,[54][55][60][61][62][63] In addition, a recently published Canadian study showed that the use of antimalarial drugs was stopped in up to 30% of patients during pregnancy. That is why we believe that our results reinforce the importance of maintaining antimalarial drugs during pregnancy.…”
Section: F I G U R E 1 Kaplan-mentioning
confidence: 99%
“…[2][3][4][5] In retrospective, prospective or population-based studies, preeclampsia has been reported between 10% and 30% of pregnancies in SLE patients. [6][7][8][9][10][11][12][13] The importance of preeclampsia consists of the fact that it is a complication associated with high maternal and fetal morbidity and mortality, mainly in developing countries. 14 In addition, an increased risk of future cardiovascular complications in both newborns and women complicated with preeclampsia has been reported.…”
Section: Introductionmentioning
confidence: 99%